PSHA of the southern Pacific Islands. Issue 3 (7th November 2020) - Johnson, K L; Pagani, M; Styron, R H
SUMMARY: The southern Pacific Islands region is highly seismically active and includes earthquakes from four major subduction systems, seafloor fracture zones and transform faults, and other sources of crustal seismicity. Since 1900, the area has experienced >350 earthquakes of M  > 7.0, including 11 of M  ≥ 8.0. Given the elevated threat of earthquakes, several probabilistic seismic hazard analyses have been published for this region or encompassed subregions; however, those that are publicly accessible do not provide complete coverage of the region using homogeneous methodologies. Here, we present a probabilistic seismic hazard model for the southern Pacific Islands that comprehensively covers the Solomon Islands in the northwest to the Tonga islands in the southeast. The seismic source model accounts for active shallow crustal seismicity with seafloor faults and gridded smoothed seismicity, subduction interfaces using faults with geometries defined based on geophysical data sets and models, and intraslab seismicity modelled by a set of ruptures that occupy the slab volume. Each source type is assigned occurrence rates based on subcatalogues classified to each respective tectonic context. Subduction interface and crustal fault occurrence rates also incorporate a tectonic component based on their respective characteristic earthquakes. We demonstrate the use of non-standard magnitude–frequency distributions to reproduce the observed occurrence rates. For subduction interface sources, we use various versions of the source model to account for epistemic uncertainty in factors impacting the maximum magnitude earthquake permissible by each source, varying the interface lower depth and segmentation as well as the magnitude scaling relationship used to compute the maximum magnitude earthquake and subsequently its occurrence rate. The ground motion characterization uses a logic tree that weights three ground motion prediction equations for each tectonic region. We compute hazard maps for 10 and 2 per cent probability of exceedance in 50 yr on rock sites, discussing the regional distribution of peak ground acceleration and spectral acceleration with a period of 1.0 s, honing in on the hazard curves and uniform hazard spectra of several capital or populous cities and drawing comparisons to other recent hazard models. The results reveal that the most hazardous landmasses are the island chains closest to subduction trenches, as well as localized areas with high rates of seismicity occurring in active shallow crust. We use seismic hazard disaggregation to demonstrate that at selected cities located above subduction zones, the PGA with 10 per cent probability of exceedance in 50 yr is controlled by M w  > 7.0 subduction interface and intraslab earthquakes, while at cities far from subduction zones, M w  < 6.5 crustal earthquakes contribute most. The model is used for southern Pacific Islands coverage in the Global Earthquake Model Global Hazard Mosaic.